Dietary patterns and risk of systemic lupus erythematosus in women. (January 2020) - Tedeschi, S K; Barbhaiya, M; Sparks, J A; Karlson, E W; Kubzansky, L D; Roberts, A L; Willett, W C; Lu, B; Costenbader, K H
Objective: Dietary intake is a complex exposure and a potential risk factor for systemic lupus erythematosus (SLE) due to its impact on lipid and glucose metabolism, oxidative stress, and the intestinal microbiome. We aimed to test whether a prudent dietary pattern is associated with a lower risk of SLE, and whether a Western dietary pattern is associated with a higher risk of SLE. Methods: We prospectively investigated two dietary patterns and SLE risk among women in the Nurses' Health Study (NHS, 1984–2014) and Nurses' Health Study II (NHSII, 1991–2015). Food frequency questionnaires were completed every four years. Congruent with prior work in NHS and NHSII, we derived two separate dietary patterns (prudent and Western) using principal component analysis within each cohort. Incident SLE was confirmed by the American College of Rheumatology's 1997 criteria. We estimated hazard ratios (HR) and 95% confidence intervals ( CI ) for SLE by dietary pattern quartiles using Cox models adjusted for time-varying covariates. Models were performed separately in each cohort and results were meta-analyzed. Stratified analyses tested the association of dietary patterns with anti-dsDNA positive SLE and anti-dsDNA negative SLE. Results: We confirmed 82 NHS incident SLE cases and 98 NHSII SLE cases during 3, 833, 054 person-years of follow-up. A higher (healthier) prudent dietary pattern score was not associated with SLE risk (meta-analyzed HRQ4 versus Q1 0.84 [95% CI 0.51, 1.38]). Women with higher (less healthy) Western dietary pattern scores did not have a significantly increased risk for SLE (meta-analyzed HRQ4 versus Q1 1.35 [95% CI 0.77, 2.35]). Results were similar after further adjustment for body mass index. Incident anti-dsDNA positive SLE and anti-dsDNA negative SLE were not associated with either dietary pattern. Conclusion: We did not observe a relationship between prudent or Western dietary pattern score and risk of SLE.